Sex, gender, and sexuality and the oral health workforce in Africa - Foláyan, Moréniké Oluwátóyìn; Okanlawon, Kehinde; Ishola, Adeyinka Ganiyat; Haire, Bridget (Frontiers in Oral Health, 2025)
This study explores how sex, gender, and sexuality intersect with Nigeria's oral health workforce crisis, highlighting structural barriers that hinder inclusion and equitable care. Nigeria faces an acute shortage of dental professionals—just 0.03 dentists per 100,000 people—amid entrenched inequities shaped by colonial, patriarchal, and heteronormative systems. Originally designed to center the voices of sexual and gender minority (SGM) oral health professionals through interviews, the study encountered complete refusal to participate. This collective silence redirected the research focus, reframing non-participation as evidence of systemic stigma, legal risk, and fear of professional ostracization. Using the frameworks of structural stigma and intersectionality, the paper argues that SGM invisibility reflects institutionalized oppression that restricts workforce diversity and perpetuates health disparities. Conventional methods that emphasize “giving voice” are critiqued for failing to address power dynamics. In response, the study proposes alternative methodologies, including researcher positionality, autoethnography, and critical discourse analysis, to analyze silence as a form of resistance and evidence of structural erasure. The paper positions that a homogeneous workforce lacking cultural competence contributes to care avoidance and delayed treatment among SGM patients, who already face higher oral disease burdens. Addressing these inequities requires systemic interventions aligned with the WHO 2022 Oral Health Resolution's call for integrated, people-centered care, including decriminalization, inclusive workplace policies, gender-balanced leadership, SGM-affirming curricula, and rural workforce investment. The study concludes that oral health equity in Africa depends on transforming entrenched power structures to cultivate a diverse, inclusive, and responsive workforce that mirrors the identities and realities of the populations it serves.